Sosialisasi Pembentukan Akhlakul Karimah Siswa Era Milenial di SMP Negeri 1 Sungai Limau Kabupaten Padang Pariaman - Andrianto Andrianto; Firda Khairati Amris; Rully Hidayatullah; Fisa Amanah (Journal of Humanity Dedication, 2023)
The background for this dedication was that there was a request from the Principal, Mrs. Yulnalita, SMP Negeri 1 Sungai Limau, Padang Pariaman Regency, that there were several cases of her students falling into promiscuity. This is inseparable from the association in the present which is called the millennial era. This service in the form of outreach aims to provide students with insight into the importance of forming akhlakul karimah students in the millennial era, insight into abilities for students about techniques and procedures for forming akhlakul karimah students and insight into knowledge for students about the importance of increasing the quality and quantity of forming akhlakul karimah students in the millennial era. This service is carried out using the method of providing material, discussing and consulting with the Principal, teachers and education staff in the school. The material presented in each session varies according to the theme. The results obtained from this activity are the formation of noble character for students of SMPN 1 Sungai Limau, Padang Pariaman Regency.